2020
DOI: 10.5114/hpr.2020.99002
|View full text |Cite
|
Sign up to set email alerts
|

A classroom-based physical activity intervention for adolescents: Is there an effect on self-efficacy, physical activity, and on-task behavior?

Abstract: health psychology report • volume 8(4),  original article background Classroom-based physical activity is a newly explored avenue for providing physical activity opportunities to children within the school, but it is one that is showing academic gains in areas such as on-task behavior. The purpose of this study was to explore the impact of pedal desks placed in high school classrooms. Three main objectives were examined: 1) the possible increase in physical activity self-efficacy among high school students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 123 publications
0
7
0
8
Order By: Relevance
“…The lifestyles of various age groups, including children, especially in their late childhood, have changed in recent years. In contrast to children a few decades ago, children today are leading increasingly sedentary lifestyles that involve greater time spent on computers and watching TV (Bidzan-Bluma and Lipowska, 2018 ; Jochimek and Łada, 2019 ; Cornelius et al, 2020 ). In the last 15 years, the Internet has grown very fast: 40% of the world's population use the Internet, and the population of children is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…The lifestyles of various age groups, including children, especially in their late childhood, have changed in recent years. In contrast to children a few decades ago, children today are leading increasingly sedentary lifestyles that involve greater time spent on computers and watching TV (Bidzan-Bluma and Lipowska, 2018 ; Jochimek and Łada, 2019 ; Cornelius et al, 2020 ). In the last 15 years, the Internet has grown very fast: 40% of the world's population use the Internet, and the population of children is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…According to the obtained results, the increase in intrinsic motivation is higher in elementary school under the condition of the cooperative learning intervention. The results of Navarro (2017) showed that the intrinsic motivation of physical education students after cooperation increased from 3.76 before treatment to 4.44, an increase of 15.3%, and the average treatment of intrinsic motivation in high school was 5% [ 54 , 55 , 56 ]. Here, the difference in favor of the control group was reported.…”
Section: Discussionmentioning
confidence: 99%
“…El sillín del dispositivo bike desk con pupitre integrado puede resultar más incómodo que una silla (Cornelius, 2018;Pilcher y Baker, 2016).…”
Section: Bike Desksunclassified
“…La sugerencia profesional y personal para este estudio de la Dr. Alicia Fedewa, autora de numerosas publicaciones que ha realizado intervenciones con bike desks en poblaciones de niños y jóvenes (Fedewa et a., 2018;Fedewa, Abel et al 2017;Fedewa, Cornelius et al 2017) y ha dirigido una tesis sobre la aplicación de bike desks con escolares (Cornelius, 2018). Esta investigadora recomendó utilizar las mini bicicletas estáticas por los problemas que ocasionaron en sus investigaciones las bicicletas con pupitre integrado para realizar tareas académicas, a excepción de leer o atender.…”
Section: Bike Desksunclassified
See 1 more Smart Citation